European burden of cancer in 2020 attributable to alcohol use. (20th October 2021) - Rumgay, H; Shield, K; Charvat, H; Ferrari, P; Lemmens, V; Rehm, J; Soerjomataram, I
Abstract: Background: Alcohol use can increase the risk of at least seven different cancer types. We present regional and national estimates of alcohol-attributable cancer burden in 2020 to inform alcohol policy and cancer control in Europe. Methods: In this population-based study, we calculated population attributable fractions (PAFs) using relative risk estimates and alcohol use prevalence by age, sex, and country. Assuming a 10-year latency period between alcohol consumption and cancer occurrence, we used alcohol consumption prevalence from 2010 and GLOBOCAN 2020 data to estimate new cancer cases attributable to alcohol consumption. We also calculated the contribution of moderate (<20 g alcohol per day), risky (20 to 60 g per day), and heavy (>60 g per day) drinking to the total alcohol-attributable cancer burden. Results: Within Europe, an estimated 181, 000, or 4%, of all new cases of cancer in 2020 were attributable to alcohol consumption. Males represented two thirds (68%) of the total alcohol-attributable cancer cases in Europe. The cancer sites which contributed the most alcohol-attributable cases were cancers of the colorectum (59, 000 cases), breast (38, 500 cases), and oral cavity (22, 000 cases). Among women in the European regions, the burden of alcohol-attributable cancers was highest in Western Europe and Northern Europe; among men, the burden was highest in Central and Eastern Europe. Heavy drinking contributed most to the burden of alcohol-attributable cancers in Europe (52% of alcohol-attributable cases), and risky and moderate drinking contributed 37% and 11%, respectively. Conclusions: Our findings highlight the need for effective policies to increase awareness of the link between alcohol use and cancer and decrease overall alcohol consumption to reduce this preventable burden of cancer in Europe. Key messages: An estimated 181, 000 cancers in Europe in 2020 were attributable to alcohol use. Effective policies are needed to increase awareness of the link between alcohol and cancer and decrease alcohol use in Europe.